2015
DOI: 10.1038/jp.2015.173
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the respiratory rate by miniature motion sensors in premature infants: a comparative study

Abstract: Monitoring RR with motion sensors is more accurate compared with the impedance, in infants, in all ventilation modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Documented measurements often diverge from accurately counted ones [ 7 ]. While there are respiratory sensors in development using a range of methods very little data is available on usage outside of controlled laboratory settings [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Documented measurements often diverge from accurately counted ones [ 7 ]. While there are respiratory sensors in development using a range of methods very little data is available on usage outside of controlled laboratory settings [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used cardiorespiratory monitoring technologies in the neonatal intensive care unit (NICU) are pulse oximetry based on photoplethysmography, electrocardiography (ECG) and impedance pneumography (IPG) based on electrical potential differences obtained through adhesive electrodes on the skin. However, IPG suffers from inaccuracy and cardiac interference in neonates with rapid respiratory rates (RRs) and limited lung aeration because it is based on breath-dependent thoracic variations in transthoracic impedance [1][2][3]. Moreover, these instruments have several additional disadvantages resulting from the use of adhesive sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant attention has been paid to non-contact novel methods for vital sign assessment in neonates [1,2,[4][5][6][7][8][9]. However, these studies either were explorative with small sample sizes or reported on techniques used to monitor only RR or HR (heart rate) [3,[10][11][12][13]. Trials for contactless cardiorespiratory simultaneous measurement have not been reported in the NICU population.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Transthoracic impedance plethysmography is susceptible to erroneous measurements, as patient movements can lead to significant interference. [6,7] Improving accuracy of respiratory monitoring will increase early detection of significant changes in clinical status, such as bradypnea in opioid overdose, and prevent adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%